1996
DOI: 10.1002/j.1460-2075.1996.tb01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Bax alpha perturbs T cell development and affects cell cycle entry of T cells.

Abstract: Bax alpha can heterodimerize with Bcl‐2 and Bcl‐X(L), countering their effects, as well as promoting apoptosis on overexpression. We show that bax alpha transgenic mice have greatly reduced numbers of mature T cells, which results from an impaired positive selection in the thymus. This perturbation in positive selection is accompanied by an increase in the number of cycling thymocytes. Further to this, mature T cells overexpressing Bax alpha have lower levels of p27Kip1 and enter S phase more rapidly in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
1
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(124 citation statements)
references
References 56 publications
(83 reference statements)
12
110
1
1
Order By: Relevance
“…In T cell populations from baxaexpressing transgenic mice, it was found that entry into S phase (from quiescence) was accelerated, in comparison to controls (Brady et al, 1996), whereas the opposite e ect (i.e., delayed S phase entry) was observed in bcl-2-expressing transgenic mice (also from a quiescent state) (O'Reilly et al, 1996). From these observations one might begin to form a model in which enhancement or attenuation of cell cycle progression is associated with pro-or anti-apoptotic members of the family, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In T cell populations from baxaexpressing transgenic mice, it was found that entry into S phase (from quiescence) was accelerated, in comparison to controls (Brady et al, 1996), whereas the opposite e ect (i.e., delayed S phase entry) was observed in bcl-2-expressing transgenic mice (also from a quiescent state) (O'Reilly et al, 1996). From these observations one might begin to form a model in which enhancement or attenuation of cell cycle progression is associated with pro-or anti-apoptotic members of the family, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Since apoptosis in other systems has been shown to be protein synthesis-dependent (Brady et al 1996b), we investigated whether mAb 225-mediated apoptosis require on-going protein synthesis. DiFi cells were treated with mAb 225 in the presence or absence of cycloheximide, and cell extracts were assayed for the induction of apoptosis.…”
Section: Mab 225-induced Apoptosis Is Accompanied By Increased Expresmentioning
confidence: 99%
“…For instance, apoptosis regulatory proteins of the Bcl-2 family have been shown to modulate cell-cycle progression. In particular, overexpression of the anti-apoptotic members of this family in B and T cells delays entry into S-phase [5][6][7] and accelerates withdrawal from the cell cycle [8,9]. In contrast, overexpression of pro-apoptotic members such as Bax or Bad in T cells of transgenic mice increases the number of cycling thymocytes, favouring entry into S-phase [6,10].…”
Section: Introductionmentioning
confidence: 99%